2020
DOI: 10.1038/s41598-020-78629-z
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor TAL1 and miR-17-92 create a regulatory loop in hematopoiesis

Abstract: A network of gene regulatory factors such as transcription factors and microRNAs establish and maintain gene expression patterns during hematopoiesis. In this network, transcription factors regulate each other and are involved in regulatory loops with microRNAs. The microRNA cluster miR-17-92 is located within the MIR17HG gene and encodes six mature microRNAs. It is important for hematopoietic differentiation and plays a central role in malignant disease. However, the transcription factors downstream of miR-17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 75 publications
0
7
0
1
Order By: Relevance
“…The most significant enrichment was of targets for E47, an activator of adiponectin expression (Doran et al, 2008). E47 regulates hematopoiesis, and its expression in blood cells could therefore determine to establish obesity-related lineages (Meyer et al, 2020). Other relevant target enrichments were for RREB1, which is also encoded by an Ow-dmCpGhosting gene, and for SREBP1, a partner of E47 in adiponectin expression activation and an extensively studied regulator of FA metabolism (Doran et al, 2008;Jump, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The most significant enrichment was of targets for E47, an activator of adiponectin expression (Doran et al, 2008). E47 regulates hematopoiesis, and its expression in blood cells could therefore determine to establish obesity-related lineages (Meyer et al, 2020). Other relevant target enrichments were for RREB1, which is also encoded by an Ow-dmCpGhosting gene, and for SREBP1, a partner of E47 in adiponectin expression activation and an extensively studied regulator of FA metabolism (Doran et al, 2008;Jump, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…showed that reduced expression of miR-92 promotes proliferation, migration, invasion and apoptosis in GBM cells by targeting neogenin (NEO1) ( 41 ). In addition, miR-92b transcription is regulated by transcription factors like TAL1-E47 during hematopoiesis and embryogenesis, SP1 during cell differentiation and apoptosis, and HiF1 during hypoxic conditions ( 42 44 ). In our study, we performed a rigorous bioinformatics analysis combined with real-time PCR, and western blots to identify potential miR-92b target genes.…”
Section: Discussionmentioning
confidence: 99%
“…The miR-17–92 cluster expression decreases during terminal erythroid differentiation, and its overexpression by targeting TAL1 negatively affects erythroid lineage differentiation [ 92 ].…”
Section: Mirna Regulation In Erythropoiesis (Table 2 ...mentioning
confidence: 99%